Depressive Symptoms and Osteoporosis in Middle-Aged and Older Adults: A Cross-Sectional Analysis of NHANES and HRS Data - Wen Zhang MS; Yi Tang MS; Lei Chen MS; Zhongyi Zhang MS; Xinyu Hu MS; Kai Cheng MS; Jiaju Zhou MS; Peijian Tong MD (Geriatric Orthopaedic Surgery & Rehabilitation)
Background & Aims Depression and osteoporosis are common among middle-aged and older adults, both impacting morbidity and quality of life. Their shared risk factors suggest a potential link, but this relationship remains underexplored. This study aimed to assess the association between depressive symptoms and osteoporosis in two large cohorts: the National Health and Nutrition Examination Survey (NHANES, 2005-2010) and Health and Retirement Study (HRS, 2012). Methods We analyzed data from adults aged ≥50 years in NHANES (n = 3612) and HRS (n = 4307). Depressive symptoms were measured using PHQ-9 in NHANES and CES-D 8 in HRS, while osteoporosis was defined by self-reported diagnosis and medication use. Generalized linear models were used to evaluate the association, adjusting for demographic, lifestyle, and comorbidity factors. Subgroup analyses and sensitivity tests were conducted to explore effect modifiers and result robustness. Results Depressive symptoms were positively associated with osteoporosis in both cohorts (NHANES: adjusted OR = 1.061, 95% CI: 1.034-1.088; HRS: adjusted OR = 1.063, 95% CI: 1.014-1.115). Significant associations were observed across subgroups, with stronger effects in individuals with diabetes and arthritis. Sex differences showed higher odds ratios for men in HRS. The relationship exhibited a linear trend, with increasing risk as depressive severity intensified. Conclusion Depressive symptoms (PHQ-9/CES-D8) significantly associate with higher osteoporosis risk in older adults, with consistent cross-sectional findings across populations. While causality remains unclear, results support clinical bone density monitoring in depression care and depression screening in osteoporosis management. Future longitudinal studies should clarify mechanisms, while public health strategies should integrate mental-bone health prevention approaches.